Screening for hypertension in adults: protocol for evidence reviews to inform a Canadian Task Force on Preventive Health Care guideline update - Shaver, Nicole; Beck, Andrew; Bennett, Alexandria; Wilson, Brenda J.; Garritty, Chantelle; Subnath, Melissa; Grad, Roland; Persaud, Navindra; Thériault, Guylène; Flemming, Jennifer; Thombs, Brett D.; LeBlanc, John; et al. (Université d'Ottawa | University of Ottawa, 2024)
Abstract Purpose To inform updated recommendations by the Canadian Task Force on Preventive Health Care on screening in a primary care setting for hypertension in adults aged 18 years and older. This protocol outlines the scope and methods for a series of systematic reviews and one overview of reviews. Methods To evaluate the benefits and harms of screening for hypertension, the Task Force will rely on the relevant key questions from the 2021 United States Preventive Services Task Force systematic review. In addition, a series of reviews will be conducted to identify, appraise, and synthesize the evidence on (1) the association of blood pressure measurement methods and future cardiovascular (CVD)-related outcomes, (2) thresholds for discussions of treatment initiation, and (3) patient acceptability of hypertension screening methods. For the review of blood pressure measurement methods and future CVD-related outcomes, we will perform a de novo review and search MEDLINE, Embase, CENTRAL, and APA PsycInfo for randomized controlled trials, prospective or retrospective cohort studies, nested case–control studies, and within-arm analyses of intervention studies. For the thresholds for discussions of treatment initiation review, we will perform an overview of reviews and update results from a relevant 2019 UK NICE review. We will search MEDLINE, Embase, APA PsycInfo, and Epistemonikos for systematic reviews. For the acceptability review, we will perform a de novo systematic review and search MEDLINE, Embase, and APA PsycInfo for randomized controlled trials, controlled clinical trials, and observational studies with comparison groups. Websites of relevant organizations, gray literature sources, and the reference lists of included studies and reviews will be hand-searched. Title and abstract screening will be completed by two independent reviewers. Full-text screening, data extraction, risk-of-bias assessment, and GRADE (Grading of Recommendations Assessment, Development and Evaluation) will be completed independently by two reviewers. Results from included studies will be synthesized narratively and pooled via meta-analysis when appropriate. The GRADE approach will be used to assess the certainty of evidence for outcomes. Discussion The results of the evidence reviews will be used to inform Canadian recommendations on screening for hypertension in adults aged 18 years and older. Systematic review registration This protocol is registered on PROSPERO and is available on the Open Science Framework (osf.io/8w4tz).